Pendampingan Persepsi Masyarakat Terhadap Implementasi Teknologi Pagar Lebah (Apis cerana) dalam Mitigasi Intervensi Gajah di Kawasan Perbatasan Taman Nasional Way Kambas (TNWK) dan Lahan Pertanian Desa Braja Yekti - Annisa Nur Fadillah; Agisni Maharani; Anjas Wa’dah Lubis; Halistin; Aisyah Musfirah; Boy Sandi Jaluasi Silalahi; Aysah Yusnia Putri; Chika Dian Asmarani; Dea Amanda; Jonathan Cristofel Siburian (Laporan Upaya Nyata Inovasi Ilmu Komputer, 2025)
Human-elephant conflict around Way Kambas National Park (TNWK) is still a serious problem that causes economic, social and even fatalities. This study aims to analyze the feasibility of implementing a bee fence by utilizing the natural behavior of elephants that are afraid with bees (Apis cerena) in the buffer village of Braja Yekti Village. The research methodology includes a field survey in Braja Yekti Village for the selection of bee fence locations, analysis of the physical environment, identification of bee food vegetation, financial analysis (BEP, R/C Ratio, NPV, and PP), as well as a study of community social conditions through questionnaires and in depth interviews. The results showed that Braja Yekti Village has ecological and socio-economic potential for bee fence development, although it still faces challenges in the form of low education levels and high risk of elephant conflict. Vegetation analysis showed sufficient bee forage availability, especially from acacia, guava and gandarussa plants, thus supporting the sustainability of honey bee colonies. Financial and social analysis confirmed that the implementation of bee fencing is economically feasible, prospective as an additional source of income, and positively supported by the majority of the community, making it a potential solution to human-elephant conflict.